Vasorelaxant Activities and its Underlying Mechanisms of Magnolia Volatile Oil on Rat Thoracic Aorta Based on Network Pharmacology - Xu, Jin-Feng; Xia, Jia; Wan, Yan; Yang, Yu; Wu, Jiao-Jiao; Peng, Cheng; Ao, Hui (Frontiers in Pharmacology, 2022)
Objective: Magnolia volatile oil (MVO) is a mixture mainly containing eudesmol and its isomers. This study was to investigate the vasorelaxant effects and the underlying mechanism of MVO in rat thoracic aortas. Method: The present study combined gas chromatography–mass spectrometry (GC-MS) and network pharmacology analysis with in vitro experiments to clarify the mechanisms of MVO against vessel contraction. A compound–target network, compound–target–disease network, protein–protein interaction network, compound–target–pathway network, gene ontology, and pathway enrichment for hypertension were applied to identify the potential active compounds, drug targets, and pathways. Additionally, the thoracic aortic rings with or without endothelium were prepared to explore the underlying mechanisms. The roles of the PI3K-Akt-NO pathways, neuroreceptors, K+ channels, and Ca2+ channels on the vasorelaxant effects of MVO were evaluated through the rat thoracic aortic rings. Results: A total of 29 compounds were found in MVO, which were identified by GC-MS, of which 21 compounds with a content of more than 0.1% were selected for further analysis. The network pharmacology research predicted that beta-caryophyllene, palmitic acid, and (+)-β-selinene might act as the effective ingredients of MVO for the treatment of hypertension. Several hot targets, mainly involving TNF, CHRM1, ACE, IL10, PTGS2, REN, and F2, and pivotal pathways, such as the neuroactive ligand–receptor interaction, the calcium signaling pathway, and the PI3K-Akt signaling, were responsible for the vasorelaxant effect of MVO. As expected, MVO exerted a vasorelaxant effect on the aortic rings pre-contracted by KCl and phenylephrine in an endothelium-dependent and non-endothelium-dependent manner. Importantly, a pre-incubation with indomethacin (Indo), N-nitro-L-arginine methyl ester, methylene blue, wortmannin, and atropine sulfate as well as 4-aminopyridione diminished MVO-induced vasorelaxation, suggesting that the activation of the PI3K-Akt-NO pathway and KV channel were involved in the vasorelaxant effect of MVO, which was consistent with the results of the Kyoto Encyclopedia of Genes and the Genomes. Additionally, MVO could significantly inhibit Ca2+ influx resulting in the contraction of aortic rings, revealing that the inhibition of the calcium signaling pathway exactly participated in the vasorelaxant activity of MVO as predicted by network pharmacology. Conclusion: MVO might be a potent treatment of diseases with vascular dysfunction like hypertension. The underlying mechanisms were related to the PI3K-Akt-NO pathway, KV pathway, as well as Ca2+ channel, which were predicted by the network pharmacology and verified by the experiments in vitro. This study based on network pharmacology provided experimental support for the clinical application of MVO in the treatment of hypertension and afforded a novel research method to explore the activity and mechanism of traditional Chinese medicine.